2020
DOI: 10.1088/1742-6596/1677/1/012085
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of bubble evolution at boiling on surfaces with different wettability

Abstract: The hybrid Lattice Boltzmann method is adopted for a detailed study of surface wettability effects on evolution of vapor bubbles and temperature field of heat exchange surface at boiling. The simulation results show that the bubble departure diameter increases with an increase of static contact angle, and its value normalized by the capillary length approaches 3 for superlyophobic surface. In the range of contact angles of 110° – 129° the size of the dry area bounded by triple contact line greatly increases co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Generally speaking, the weak wetting surface have larger effective nucleation hole size range and higher nucleation center density to improve boiling heat transfer performance under low heat flux. Fedoseev et al (2020) also showed that enhancement of heat transfer observed on weak wetting boiling surface because to the increasing nucleation site density and the decreasing boiling onset temperature by Lattice Boltzmann simulation. Meanwhile, they also analyzed the dry areas on the weak wetting surface.…”
Section: Effect Of the Weak Wetting Surface On Heat Transfermentioning
confidence: 78%
“…Generally speaking, the weak wetting surface have larger effective nucleation hole size range and higher nucleation center density to improve boiling heat transfer performance under low heat flux. Fedoseev et al (2020) also showed that enhancement of heat transfer observed on weak wetting boiling surface because to the increasing nucleation site density and the decreasing boiling onset temperature by Lattice Boltzmann simulation. Meanwhile, they also analyzed the dry areas on the weak wetting surface.…”
Section: Effect Of the Weak Wetting Surface On Heat Transfermentioning
confidence: 78%